Bermudan options pricing formulas in uncertain financial markets. (November 2021) - Pan, Zeyu; Gao, Yin; Yuan, Lin
Abstract: Bermudan options, including Bermudan call option and Bermudan put option, as a kind of financial derivatives provide a series of exercise dates for holder before the expiration time, which can be seen as the combination of European options and American options. This paper investigates the pricing problem of Bermudan options in uncertain financial markets. By means of the extreme value theorems, the generalized pricing formulas of Bermudan options are derived. Apply uncertain stock model to describe the stock price, the explicit pricing formulas of Bermudan options are obtained. Besides, some numerical examples are discussed in this paper.